Efficacy and safety of a popular thermogenic drink after 28 days of ingestion - Stout Jeffrey R; Hassell Scott E; Dalbo Vincent J; Roberts Michael D; Kerksick Chad M (Taylor & Francis Group, 2008)
Abstract Background We have recently demonstrated that consuming a thermogenic drink (TD) acutely increases energy expenditure and serum markers of lipolysis in healthy, college-aged individuals. The purpose of this study was to determine if consuming TD over 28 days affects its acute thermogenic and lipolytic effects as well as body composition and clinical chemistry safety markers. Methods Sixty healthy, males (mean ± SE; 23 ± 1 years, 177 ± 2 cm, 81.7 ± 2.1 kg, 22.8 ± 1.4% body fat; n = 30) and females (23 ± 1 years, 166 ± 2 cm, 62.1 ± 1.8 kg, 28.3 ± 1.4% body fat; n = 30) reported to the laboratory on day 0 (T1) for determination of body composition, resting energy expenditure (REE) as well as glycerol and free fatty acid (FFA) levels before and after ingesting either 336 ml of TD or a non-caloric, non-caffeinated placebo (PLA) drink. Following day 0, participants supplemented daily with 336 ml·day-1 of either TD or PLA and repeated identical testing procedures on day 28 (T2). Day 28 area under the curve (AUC) values were calculated for REE, FFA, and glycerol. Day 28 acute data and prolonged AUC comparisons between groups were analyzed using ANOVAs with repeated measures. Results Percent body fat (p = 0.02) and fat mass (p = 0.01) decreased in the TD group compared to the PLA group after 28 days. Day 28 FFA AUC values (p = 0.048) were greater in the TD group compared to the PLA group. There was no significant difference in day 28 REE AUC values (p = 0.30) or glycerol AUC values (p = 0.21), although a significant increase in REE values in the PLA group may have confounded these findings. There were no differences between groups concerning blood and clinical safety markers. Conclusion Within-group elevations in FFA and REE values in the TD group were still evident following a 28-day supplementation period which may contribute to the observed decrements in %BF. Further, prolonged TD supplementation did not alter the assessed clinical safety markers. Future studies should examine the synergistic and independent effects of the active ingredients in addition to effects of longer ingestion periods of TD ingestion with or without exercise at promoting and sustaining changes in body composition.